Humic extracts of hydrochar and Amazonian Dark Earth: Molecular characteristics and effects on maize seed germination - Bento, Lucas Raimundo [UNESP] (2020)
Inspired by the presence of anthropogenic organic matter in highly fertile Amazonian Dark Earth (ADE), which is attributed to the transformation of organic matter over thousands of years, we explored hydrothermal carbonization as an alternative for humic-like substances (HLS) production. Hydrothermal carbonization of sugarcane industry byproducts (bagasse and vinasse) in the presence and absence of H3PO4 afforded HLS, which were isolated and compared with humic substances (HS) isolated from ADE in terms of molecular composition and maize seed germination activity. HLS isolated from sugarcane bagasse hydrochar produced in the presence or absence of H3PO4 comprised both hydrophobic and hydrophilic moieties, differing from other HLS mainly in terms of phenolic content, while HLS isolated from vinasse hydrochar featured hydrophobic structures mainly comprising aliphatic moieties. Compared to that of HLS, the structure of soil-derived HS reflected an increased contribution of fresh organic matter input and, hence, featured a higher content of O–alkyl moieties. HLS derived from lignocellulosic biomass were rich in phenolics and promoted maize seed germination more effectively than HLS comprising alkyl moieties. Thus, HLS isolated from bagasse hydrochar had the highest bioactivity, as the presence of amphiphilic moieties therein seemed to facilitate the release of bioactive molecules from supramolecular structures and stimulate seed germination. Based on the above results, the hydrothermal carbonization of lignocellulosic biomass was concluded to be a viable method of producing amphiphilic HLS for use as plant growth promoters.